A emancipação nas relações de poder em um currículo organizado em ciclos - Ferreira, Eucaris Joelma Rodrigues (2011)
In this research I am questioning the emancipation in the curriculum politic organized in cycles, from questions that involve the responsibility for teaching social emancipation, and the purpose and possibility of realization of emancipation through the curricular politic organized in cycles. I delimit as study object the emancipation in the curriculum politic organized in cycles in the School Irenice Godoy de Campos e Silva, from the municipal education of Varzea Grande - MT. The main objective of this research is to understand and identify the emancipation in the curriculum politic organized in cycles, considering it a space for construction of an understanding of emancipation in curricular field. In accordance with theoretical and methodological, became necessary the articulation between the approach of the politic cycle (BALL, 1994) with the understanding of cyclical construction of curriculum politic, and the theory of discourse (LACLAU and MOUFFE, 1985) with understanding of the politic as discursive field, area of articulatory practice and power production. The data collection was carried by bibliographic sources, documentary and oral, with analysis of consubstantiation documents about the curriculum politic in analysis and interviews with teachers and graduated students. The understanding of emancipation was contextualized from a rereading of different contexts, where they addressed the relationship between emancipation and subjectivity (HALL, 2006), the rise of emancipation in curricular field by critical theory of curriculum (MOREIRA, 1990; SILVA, 1999), the emancipation and curriculum in Brazil (FREIRE, 1986, 2005, 2009) and the contemporary understanding of emancipation (LACLAU, 1996). The link between politic cycle and the theory of speech enabled us to understand that in the curriculum politic organized in cycles by analyzed school, the notions of curriculum, power, and emancipation are (re)meaned in curricular speeches that are the cyclic contexts. This same curriculum politic also represents a space for cultural practice (OLIVEIRA, 2005), discursive field, place of confrontation, and dispute between serial and organized curriculum in cycles per hegemony, where the curriculum speeches set for agony (MOUFFE, 2003) and the senses of emancipation are produced in such a way, on relational and contingent terms.